Aid distribution and the MDGs - Baulch, Bob (2006)
Examines whether the major bilateral and multilateral donors distribute their aid in accordance with the Millennium Development Goals (MDGs). Utilizes aid concentration curves for monetary poverty, child malnutrition, primary school enrollments, and under-five mortality to assess whether aid is distributed to the poorest and most deprived countries.